Building resilience through “Open Source Seed Systems” for climate change adaptation in Kenya, Uganda, and Tanzania: What are the options for policy? - Otieno, G.; Westphal, I. (2018)
This Policy Brief is a result of a series of national and regional stakeholder consultations and a policy write shop on the establishment and maintenance of Open Source Seed Systems that ensure inclusivity of farmers and enhance freedom to develop, access, and use plant genetic materials. The brief is also based on results from research on seed networks and policy and legislative frameworks in Kenya, Uganda, and Tanzania. The stakeholders recommend the following policy options for successful establishment and implementation of Open Source Seed Systems.